Finding Kicking Range of Sepak Takraw Game: A Fuzzy Logic Approach - Andino Maseleno; Md. Mahmud Hasan (Institute of Advanced Engineering and Science, 2015)
This paper presents a method to find kicking range of sepak takraw game when player kicks backthe ball to the other team. To serve, one player stands in the right semi-circle on their side of the court. Theplayer throws the ball to the server, who stands in the circle on their side of the court. The player kicks theball up and over the net then opponent player kicks back the ball. This research works considered how fuzzylogic can be applied for the sepak takraw game - for addressing uncertainty in kicking range of the ball. Wehave chosen Tsukamoto’s fuzzy reasoning scheme, because the individual rule outputs are crisp numbers,and therefore, the functional relationship between the input vector and the system output can be relativelyeasily identified. The result reveals that if player serve far, kicking range will be decreased and stable duringkicking very near through kicking very far. DOI: http://dx.doi.org/10.11591/telkomnika.v14i3.7833